2019
DOI: 10.3329/cardio.v12i1.43420
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice towards Dietary Salt Intake among Nurses Working in a Cardiac Hospital in Bangladesh Sciences

Abstract: Background: Noticeable proportion of Bangladeshi population including health professionals is habituated with excessive salt intake although having a good knowledge and attitude. There is no related data regarding salt intake practice among nurses in Bangladesh. The aim of this study was to assess the knowledge, attitude and practice towards dietary salt intake among the nurses working in a selected cardiac hospital. Methods: A cross-sectional study was conducted among 211 nurses working in National Hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
4
3
0
Order By: Relevance
“…This could be a main deterrent and a crucial knowledge gap that affect Sri Lanka's efforts to implement the NSRS's aim to reduce population level dietary salt consumption. It was also noted that this finding is compatible with findings of the studies in other LMICs 14, [16][17][18]21 . Furthermore, the indirect estimation of daily dietary salt consumption in our study showed that Sri Lankans consume higher than the daily requirement of salt.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This could be a main deterrent and a crucial knowledge gap that affect Sri Lanka's efforts to implement the NSRS's aim to reduce population level dietary salt consumption. It was also noted that this finding is compatible with findings of the studies in other LMICs 14, [16][17][18]21 . Furthermore, the indirect estimation of daily dietary salt consumption in our study showed that Sri Lankans consume higher than the daily requirement of salt.…”
Section: Discussionsupporting
confidence: 91%
“…Based on a desk review of published literature on surveys with similar objectives [12][13][14][15][16][17][18] , we developed an interviewer administered multicomponent knowledge, attitude, and practice survey questionnaire on salt and health as an online version using EpiCollect5 free data gathering platform 19 . in the present study, we estimated the approximate amount of per capita dietary salt of the households of adults included in the study by inquiring into the amount of monthly purchases of salt to the households and the number of household members.…”
Section: Study Instrumentmentioning
confidence: 99%
“…The results indicated that participants' per capita consumption of salt was 9.2 g/day which is almost double the recommended daily requirement of salt. This finding is compatible with the findings of studies in western countries as well as other LMICs where average per capita salt consumption varies from 9 to 12 g/day (14,(16)(17)(18)(20)(21). A reason for this could be that majority of Sri Lankan adults (59.9%) and adolescents (60.4%) were not adequately aware of the recommended daily salt consumption.…”
Section: Discussionsupporting
confidence: 91%
“…Based on a desk review of published literature on surveys with similar objectives (12)(13)(14)(15)(16)(17)(18), we developed an interviewer administered multicomponent knowledge, attitude and practice survey questionnaire on salt and health as an online version using EpiCollect5 free data gathering platform (19). We estimated the approximate per capita dietary salt intake indirectly based on the amount of monthly purchases of salt to the households and calculating per capita salt consumption according to the number of household members consuming the amount of purchased salt.…”
Section: Methodsmentioning
confidence: 99%
“…This climatic issue might be an important reason for noticeable CKD prevalence in the non-exposed area. In addition, although the added salt intake behavior during meals has been found significantly higher among the exposed population, however the proportion of this behavior among the exposed population is consistent with the prevalence found from other domestic studies [ 33 36 ]. Therefore, the inconsistent proportion of this behavior in the non-exposed population might be due to the underreporting or past use.…”
Section: Discussionsupporting
confidence: 89%